Mandibular Distal Extension Cast Partial Denture Using Corrective Cast Technique V/S Maxillary Tooth Supported Overdenture: A Case Report - Singh, Geetanjali; Sharma, Sunny; Gill, Harvinder Singh (International Journal Of Drug Research And Dental Science, 2020)
Dentures requiring support from teeth, mucosa, and the underlying alveolar ridges are liable to be displaced under occlusal forces that adversely affect the abutments and residual ridge during function and parafunction. In the case of free end saddles like Keneddy’s class I and Keneddy’s class II treatment and maintenance it is a very common challenge for the clinician as mucosa gets displaced under load and distal extension. These dentures only have partial support from teeth as their bases act as extensions and cover ridge distal to the last abutment tooth and the residual ridge provides main support, stability, and retention. So, altered cast technique was employed for mandibular distal extension partially edentulous arches to prevent this by making an impression of mucosa under controlled pressure. Border molding was carried out on base plate made in self-cured resins, Impression was made and during lab procedures, free saddle areas were altered in the master cast. The denture was positioned on the model and the final impression was poured. The resulting model represents a corrected cast with free end saddle areas recorded under functional load. Denture construction then follows the conventional technique.